Evaluation of the In Vitro Oral Wound Healing Effects of Pomegranate (Punica granatum) Rind Extract and Punicalagin, in Combination with Zn (II) - Vildan Celiksoy (Biomolecules, 2020)
Pomegranate (Punica granatum) is a well-established folklore medicine, demonstrating benefits in treating numerous conditions partly due to its antimicrobial and anti-inflammatory properties. Such desirable medicinal capabilities are attributed to a high hydrolysable tannin content, especially punicalagin. However, few studies have evaluated the abilities of pomegranate to promote oral healing, during situations such as periodontal disease or trauma. Therefore, this study evaluated the antioxidant and in vitro gingival wound healing effects of pomegranate rind extract (PRE) and punicalagin, alone and in combination with Zn (II). In vitro antioxidant activities were studied using DPPH and ABTS assays, with total PRE phenolic content measured by Folin–Ciocalteu assay. PRE, punicalagin and Zn (II) combination effects on human gingival fibroblast viability/proliferation and migration were investigated by MTT assay and scratch wounds, respectively. Punicalagin demonstrated superior antioxidant capacities to PRE, although Zn (II) exerted no additional influences. PRE, punicalagin and Zn (II) reduced gingival fibroblast viability and migration at high concentrations, but retained viability at lower concentrations without Zn (II). Fibroblast speed and distance travelled during migration were also enhanced by punicalagin with Zn (II) at low concentrations. Therefore, punicalagin in combination with Zn (II) may promote certain anti-inflammatory and fibroblast responses to aid oral healing.